Educating for professionalism : creating a culture of humanism in medical education - Wear, Delese; Bickel, Janet W. (University of Iowa Press, 2000)
The thirteen essays in Educating for Professionalism examine the often conflicting ethical, social, emotional, and intellectual messages that medical institutions send to students about what it means to be a doctor. Because this disconnection between what medical educators profess and what students experience is partly to blame for the current crisis in medical professionalism, the authors offer timely, reflective analyses of the work and opportunities facing medical education if doctors are to win public trust. In their drive to improve medical professionalism within the world of academic med.